PERAN PIMPINAN PESANTREN DALAM MENDISIPLINKAN PELAKSANAAN SHALAT BERJAMAAH SANTRI - Mukhlishah; Ibrohim, M.Ag., Dr. Iim; Murdani, Beni (Bayani, 2024)
Pesantren is an Islamic educational institution that has dormitories and aspires to produce the nation's successor students who have righteous creeds, true jurisprudence and noble morals and always become role models for the surrounding community. The formation of personality character that is emphasized in pesantren is a disciplined character, especially in the discipline of worship. The worship that gets the most attention from the leade pesantren is congregational prayer, because congregational prayer teaches the value of obedience and discipline while teaching the value of togetherness with others. Currently, the character of student discipline, especially in the discipline of congregational prayer, is less than optimal. Based on the observations of previous researchers at the Pesantren Kampung Quran Learning Center, there are still students who are not disciplined in carrying out congregational prayer activities such as not participating in congregational prayer activities on time. The initial findings when students are not disciplined in carrying out congregational prayer activities will have an impact on other activities such as teaching and learning activities in class, devotional work activities and Quran halaqa activities become undisciplined and students become less obedient to the rules of pesantren order. This is because prayer is the core of a Muslim's life activities, so if the prayer is good, then the life is good, but if the prayer is not good, then the life is not good. This is the background of researchers to conduct research at the Pesantren Kampung Quran Learning Center with the research title "The Role of leader Pesantren in Disciplining the Implementation of Congregational Prayers." This study aims to determine how the impact of the role of Islamic boarding school leader in disciplining the implementation of congregational prayer by identifying: 1). Implementation of Congregational Prayer of Santri, 2). The Role of leader Pesantren in Disciplining the Implementation of Congregational Prayer of Santri, 3). Supporting and inhibiting factors of the role of leader pesantren in disciplining congregational prayers, 4). The impact of the role of Islamic boarding school leader in disciplining the implementation of congregational prayers, 5). The benefits of the discipline of praying in congregation. The method used in this study is qualitative research method with case studies. The data sources used in this study are primary data sources and secondary data sources. Data collection techniques in this study used observation, interview and documentation techniques. The technical data analysis used in this study is data reduction, data presentation and data analysis. The results showed that the role of Islamic boarding school leader had a good influence in improving the discipline of congregational prayer. This is shown by the increasing discipline of congregational prayer in terms of: 1). Punctuality, 2). Consistency, 3). Order in congregational prayer.